INTENSIFIERS IN ITALIAN IN TRANSIT: TRACING BIOGRAPHICAL EXPERIENCES THROUGH LANGUAGE PRACTICES (Italiano LinguaDue, 2025)
This paper explores strategies of morphological/lexical intensification in Italian-based multilingual practices I label ‘Italian in Transit’ (IiT). IiT is informally acquired by plurilingual migrants and refugees in Italy and occasionally reactivated after onward migration. This study draws on 23 interviews with IiT speakers from sub-Saharan West Africa working as street vendors in a Berlin park. After outlining the intensifiers used in my corpus, I focus on two largely interchangeable forms in Italian: molto and tanto ‘very/much/many’. In reverse to their distribution across all registers in reference corpora for spoken Italian, tanto significantly outnumbers molto in my data (though their part-of-speech distribution matches that of the target language). This predominance reflects the frequency patterns of the two intensifiers in informal spoken registers only. Thus, it may be a linguistic trace of the input participants were mainly exposed to in Italy and their biographical experiences. In contrast, other sociolinguistic factors, like the length of stay in Italy or Germany, show no decisive impact. The paper also examines the occasional use of troppo ‘too much/many’ to convey high intensity rather than excess. IiT partly shares this feature with Italian youth varieties, colloquial French, and some Italian-based contact varieties developed outside Italy. Despite considerable interspeaker variation, troppo usually occurs in re-elaborative sequences and is often preceded by strategic pauses. Its overextension – also observed in non-French-speaking participants – is therefore linked to its discourse-pragmatic and prosodic salience. Intensificatori in italiano in transito: tracciare esperienze biografiche attraverso le pratiche linguisticheQuesto contributo esplora le strategie di intensificazione morfologica/lessicale in pratiche multilingui a base italiana, per cui propongo l’etichetta ‘Italiano in Transito’ (IiT). Competenze in IiT sono acquisite in contesti informali da persone migranti e rifugiate plurilingui in Italia e occasionalmente riattivate dopo successiva migrazione. Lo studio si basa su 23 interviste con parlanti di IiT provenienti dall’Africa occidentale subsahariana, che lavorano come venditori ambulanti in un parco berlinese. Dopo aver fornito una panoramica degli intensificatori usati nel mio corpus, mi concentro su due forme ampiamente intercambiabili in italiano: molto e tanto. Contrariamente alla loro distribuzione in tutti i registri in corpora di riferimento per l’italiano parlato, tanto supera significativamente molto nei miei dati (sebbene la loro distribuzione per parte del discorso rispecchi quella della lingua target). Questa predominanza riflette la frequenza d’uso dei due intensificatori solo nei registri di parlato informale. Pertanto potrebbe essere una traccia a livello linguistico dell’input a cui i partecipanti sono stati principalmente esposti in Italia e, quindi, delle loro esperienze biografiche. Invece, altri fattori sociolinguistici, come la durata del soggiorno in Italia o in Germania, non hanno un impatto decisivo. Il contributo esamina inoltre l’uso occasionale di troppo per esprimere grande intensità anziché eccesso. L’IiT condivide in parte questo tratto con varietà giovanili di italiano, il francese colloquiale e alcune varietà di contatto a base italiana sviluppatesi fuori d’Italia. Nonostante l’alta variazione interparlante, troppo compare generalmente in sequenze rielaborative ed è spesso preceduto da pause strategiche. Perciò la sua sovraestensione – osservata anche tra parlanti non francofoni – è ricondotta alla sua salienza discorsiva e prosodica.